2020
DOI: 10.5194/acp-20-3905-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sources of volatile organic compounds and policy implications for regional ozone pollution control in an urban location of Nanjing, East China

Abstract: Abstract. Understanding the composition, temporal variability and source apportionment of volatile organic compounds (VOCs) is necessary for determining effective control measures to minimize VOCs and their related photochemical pollution. To provide a comprehensive analysis of VOC sources and their contributions to ozone (O3) formation in the Yangtze River Delta (YRD) – a region experiencing the highest rates of industrial and economic development in China – we conducted a 1-year sampling exercise using a the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 58 publications
6
27
1
Order By: Relevance
“…As shown in Fig. 7, their contributions to the total OFP are different in different areas (Duan et al, 2008;Deng et al, 2019;Fu et al, 2020;Zhao et al, 2020;Zhou et al, 2020;Zhu et al, 2020). Contributions of the top eight NMVOCs to OFP account for 51%−69% of the total, among which OVOCs, especially formaldehyde and acetaldehyde, contribute more to OFP in megacities.…”
Section: Key Photochemical Activitymentioning
confidence: 98%
“…As shown in Fig. 7, their contributions to the total OFP are different in different areas (Duan et al, 2008;Deng et al, 2019;Fu et al, 2020;Zhao et al, 2020;Zhou et al, 2020;Zhu et al, 2020). Contributions of the top eight NMVOCs to OFP account for 51%−69% of the total, among which OVOCs, especially formaldehyde and acetaldehyde, contribute more to OFP in megacities.…”
Section: Key Photochemical Activitymentioning
confidence: 98%
“…Air Act has shown that the benefit/cost ratio exceeds 40/1. 24 49 In Beijing, this measure of ozone has been larger with values just below 100 ppb in recent years. 52 The United Nations report on air pollution in Beijing states "Ozone pollution has not been effectively controlled in recent years".…”
Section: Regulatory Standards and Health Guidelinesmentioning
confidence: 99%
“…63 China is moving forward with new regulations designed to reduce VOC emissions. 20,49 Recent research shows that ozone generation in Nanjing can be reduced by controlling VOC emissions. 49 A study of sources of VOC emissions shows that many of the emissions are associated with transportation.…”
Section: Improving Air Qualitymentioning
confidence: 99%
See 2 more Smart Citations